(untitled) (Journal of Medicine, 2016)
Ankylosing Spondylosis (AS) is a chronic inflammatory disorder of joints predominantly affecting the sacroiliac joints and spine. Besides the joints, it affects many extra articular sites like heart, eye, lungs etc. Neurological complication is very rare in AS. Here we report a case of a 30 years old man of AS with peripheral neuropathy. J MEDICINE January 2016; 17 (1) : 36-38